Candida antarctica lipase A effectively concentrates DHA from fish and thraustochytrid oils - TO Akanbi; Colin Barrow (2017)
The fatty acid selectivity of Candida antarctica lipase A (CAL-A) was applied to produce DHA concentrate by controlling the rate and extent of hydrolysis. Calcium was utilized to achieve a higher degree of hydrolysis. CAL-A was not regioselective but rather fatty acid selective, showing sequential selectivity for saturated, monounsaturated and polyunsaturated fatty acids in the order of increasing double bonds. Based on its strong initial preference for saturates, CAL-A was used to concentrate 82% docosahexaenoic acid (DHA) and 11% omega-6 docosapentaenoic acid (DPA-n6) after partial hydrolysis of algal oil. Thermomyces lanuginosus (TL 100L) lipase was used to partially remove DPA-n6, further concentrating DHA to 89%. CAL-A was immobilized on octadecyl-activated resin without altering its fatty acid selectivity.